2003
DOI: 10.1002/hyp.1213
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared spectroscopy of a hydroecological indicator: new tool for determining sustainable yield for Floridan aquifer system

Abstract: Abstract:Pond-cypress (Taxodium ascendens Brong.) is a dominant canopy species in depressional wetlands of the south-eastern Coastal Plain. Unsustainable withdrawals from the karst Floridan aquifer system have caused premature decline and death of pond-cypress trees, presumably owing to altered hydroperiods (which alter the flow of water and nutrients in trees). There has been no scientifically based means to determine sustainable yield from this regional aquifer system or to detect early stages of physical/ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…In an attempt to evaluate areas that could be more susceptible to experiencing adverse environmental impacts from mining and other groundwater alterations, such as those described by Bacchus (2006) and Bacchus et al (2003), ground reconnaissance was conducted for this study prior to the georectification of features mapped as lineaments in the study area and the mapping of modern sinkholes in the study area from the state's sinkhole database. Some of the procedural steps recommended by Ogden (1984) for sinkhole analysis also were used as guidance in selecting areas for ground reconnaissance for adverse environmental impacts in the vicinity of the mine sites.…”
Section: Analyses Of Fractures and Modern Sinkholesmentioning
confidence: 99%
See 3 more Smart Citations
“…In an attempt to evaluate areas that could be more susceptible to experiencing adverse environmental impacts from mining and other groundwater alterations, such as those described by Bacchus (2006) and Bacchus et al (2003), ground reconnaissance was conducted for this study prior to the georectification of features mapped as lineaments in the study area and the mapping of modern sinkholes in the study area from the state's sinkhole database. Some of the procedural steps recommended by Ogden (1984) for sinkhole analysis also were used as guidance in selecting areas for ground reconnaissance for adverse environmental impacts in the vicinity of the mine sites.…”
Section: Analyses Of Fractures and Modern Sinkholesmentioning
confidence: 99%
“…Some of the procedural steps recommended by Ogden (1984) for sinkhole analysis also were used as guidance in selecting areas for ground reconnaissance for adverse environmental impacts in the vicinity of the mine sites. Figure 9 shows the numbered Global Positioning System (GPS) locations of some of those areas of ground reconnaissance that were identified using U.S. Geological Survey (USGS) topographic maps and established hydroecological indicators of groundwater alterations, such as those described by Bacchus et al (2003), and knowledge from other sites in Florida where adverse environmental impacts occurred from mining and other groundwater alterations. In all cases, adverse environmental impacts were identified at the ground reconnaissance locations where greater susceptibility was predicted.…”
Section: Analyses Of Fractures and Modern Sinkholesmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that natural depressional wetlands that are characteristic of the FAS (e.g., pond-cypress wetlands and wet prairies) have historic surfacewater connections to navigable waters and occur in relict sinkholes that are aligned along fractures and connected to the underlying regional karst aquifer system, as summarized by Bacchus (1998;2006;2007) and Bacchus et al (2003). Therefore, The ruling simply clarified that CWA jurisdiction did not include that man-made mine pit, simply because the mine pit included wetlands and migratory birds were utilizing that area.…”
Section: Geographically Isolated Vs Hydrologically Connected Wetlandsmentioning
confidence: 99%